MARKETING STRATEGY ANALYSIS ON FOOD PRODUCTS - Sumartini, Lilis Cucu (Moneter: Jurnal Keuangan dan Perbankan, 2023)
The economy places a great deal of importance on marketing, which is also essential to business actors' success. In this case, a well-thought-out marketing strategy is required in order for the anticipated results to be achieved. The goal of the research is to understand food items' marketing strategies. The study employs a qualitative description methodology, gathering data via observation, documentation, and interviews. The findings demonstrated that the marketing mix study discovered that the product remains straightforward, the pricing is reasonably low, the place of sale is less fancy, and the promotion is still not aggressive. The product's strengths stem from its regionally typical raw materials, while its weaknesses are related to its simple toppings and ekmasan. The product's quality raw materials and lack of preservatives present an opportunity, while its growing number of similar products and increasingly diverse variants pose a threat. The product can be used to win the competition because of its strengths and possibilities, but in order to compete with similar products, it must promptly address its flaws and threats.